Out of the box: Making space for everyday critical pedagogies. (26th April 2013) - Martin, Gregory; Brown, Tony
Abstract : Under the sway of neoliberal forces, the university system is being reconfigured to produce certain types of knowledges, imaginaries, subjectivities, and practices informed by market imperatives. Considerable literature details the promises and perils of neoliberalism in higher education. In the past decade, this has included the growth of interdisciplinary scholarship that explores the potential of critical pedagogy as a site of contestation in the higher education sector. In this context, the notion of critical pedagogy provides a dialogical and imaginative starting point for opening up spaces for what is otherwise denied or ignored. Although critical pedagogy is a "big tent" movement, a number of cogent and hard‐hitting critiques have emerged highlighting its theoretical and political limitations. Concerns include the need for more attention to the complexities of how critical pedagogies are embodied or performed. This article argues that the performative dimension of critical pedagogy is important for putting into place the production of everyday spaces capable of transforming the boundaries of what is regarded as valid or legitimate knowledge and culture.